Emotional Intelligence as Predictor of Mental, Social, and Physical Health in University Students - Extremera, Natalio; Fernández-berrocal, Pablo (The Spanish Journal of Psychology, 2006)
This study examined the association between emotional intelligence (EI), anxiety, depression, and mental, social, and physical health in university students. The sample was made up of 184 university students (38 men and 146 women). EI was evaluated by the Trait Meta-Mood Scale (Salovey, Mayer, Goldman, Turvey, & Palfai, 1995), which evaluates the three dimensions (Attention, Clarity, and Mood Repair). Anxiety was evaluated with the Trait Anxiety Questionnaire (Spielberger, Gorsuch, Lushene, Vagg, & Jacobs, 1983) and depression with the Beck Depression Inventory (Beck, Rush, Shaw, & Emery, 1979). Mental, social, and physical health were evaluated with the SF-12 Health Survey (Ware, Kosinski, & Keller, 1996). Results showed that high Emotional Attention was positively and significantly related to high anxiety, depression, and to low levels of Role Emotional, Social Functioning, and Mental Health. However, high levels of emotional Clarity and Mood Repair were related to low levels of anxiety and depression, high Role Physical, Social Functioning, Mental Health, Vitality, and General Health. This study confirmed the predictive value of Attention, Clarity and Mood Repair regarding the levels of anxiety, depression, and areas related to mental, social, and physical health in university students.
Keywords: Emotional intelligence; Anxiety; Depression; Social; Physical health